A9 BACTERIAL BILE SALT HYDROLASE GENE ABUNDANCE IS ASSOCIATED WITH RORC GENE EXPRESSION IN INTESTINAL MUCOSA OF INFLAMMATORY DISEASE PATIENTS. (26th February 2020) - Hernandez-Rocha, C; Borowski, K; Turpin, W; Smith, M; Stempak, J; Silverberg, M S
Abstract: Background: The role of gut microbes involved in bile acid metabolism and their impact on mucosal immune regulation is beginning to be appreciated. For instance, changes in microbial bile salt hydrolase (BSH) activity which deconjugates bile acids in the gastrointestinal tract of gnotobiotic mice, significantly alters gene expression patterns of immune-related genes in ileum. Moreover, bile acid dysmetabolism may participate in the chronic inflammation loop of Inflammatory bowel disease (IBD). Aims: We carried out an integrated mucosal microbiome-transcriptome analysis to elucidate associations between microbial bile-acid metabolizing function and host gene expression. Methods: Crohn's disease (CD), ulcerative colitis (UC) and IBD unclassified (IBDU) patients were recruited prior to scheduled colonoscopy performed as part of clinical care. Only patients with non-inflamed mucosa defined as a segmental simple endoscopic score 0–2 in CD and a segmental Mayo endoscopic score of 0 in UC/IBDU were included in this analysis to minimize the effect of inflammation on gene expression. Biopsy samples were obtained from terminal ileum, ascending colon and sigmoid colon, and microbial DNA and human RNA was extracted. V4 region of 16S rRNA gene was sequenced and the relative abundance of bile acid-metabolizing genes was inferred using PICRUSt. RNA-seq was used to sequence total human RNA and a supervised transcript reduction analysis focus upon 65 genes previously associated with bile acid metabolism and IBD was utilized. Associations between microbiome clusters of orthologous groups (COGs), transcriptome, diagnosis (CD vs UC/IBDU), and biopsy site were analyzed using linear mixed-effects model with lmer4 function in R. An adjusted-p value after false discovery rate correction < 0.05 was considered significant. Results: A total of 126 samples from 86 subjects were analyzed corresponding to 35 CD and 51 UC/IBDU. Mean age for the total cohort was 34.7 ± 11 years and 35 (40.6%) were females. There was a significant negative correlation between relative abundance of bacterial bsh genes (COG3049) and human RORC gene (p < 0.03). This association was independent of type of diagnosis and biopsy site. There was no association among other analyzed bacterial COGs and host genes. Conclusions: Using an integrative microbiome-host transcriptome approach, our data provide new evidence linking microbial bile acid deconjugation ( bsh genes) and host gene expression in the mucosal-luminal interface in quiescent IBD-affected tissue. Nuclear receptor RORC is pivotal in the differentiation and function of innate lymphoid cells and T-helper 17 cells. Modulation of this pathway by bile acids or gut bacteria involved in their metabolism could shed light on the immune role of bile acids in IBD patients. Funding Agencies: CAG, CIHRNational Institute of Diabetes and Digestive and Kidney Diseases (NIDDK)